In vivo phenotypic screening of selected medicinal plants for inhibition of the WNT - Ocfemia, Gio Martin A. (Gio Martin A. Ocfemia, 2018)
A mutation in the Wingless (Wnt) pathway is a major contributor to a plethora of diseases in humans such as cancer. Hence, screening for inhibitors of the pathway are crucial methods in making drugs that can cure such diseases. Using zebrafish (Danio rerio) as a model organism, an in vivo phenotypic screening of medicinal plants was conducted. Embryos at 4.5 hours post-fertilization (hpf) were subjected to 375 mM LiCl in chemically inducing B-catenin; GSK3 will be inhibited to activate the Wnt pathway which causes the eyeless phenotype. Lithium-treated embryos were exposed to 50 and 100 ug/mL extracts in 1% DMSO at about 4.7 hpf. Eye recovery was seen at the prim-5 stage (24 hpf), while other developmental defects became clearer at longpec stage (48 hpf) until protruding-mouth stage (72 hpf). Wnt inhibition was expressed among Annona muricata, Arcangelisia flava (L.) Merr., Avicennia officinalis, and Syzigium polycephaloides at 100 ug/mL. Out of all positive results, the leaf crude extract of A. muricata showed the highest recorded mortality to the zebrafish embryos. The stem crude extract of A. flava had the best inhibitory response with the lowest mortality rate but showed toxicity which manifested as developmental defects such as heart edema. The stems of this plant species are reported to contain flavanoids, alkaloids, steroids, tannins, saponins, and quinones. Its main compound, berberine, has been reported to inhibit the Wnt/B-catenin signaling pathway. Characterization, isolation, and purification of this plant is recommended to determine other possible causes of the inhibitory response.